The role of Self Help Groups on coastal indebtedness in marine fisheries sector – a case study from Kerala, south India - Vipinkumar, V.P.; Salim, Shyam S.; Pushkaran, K. N.; Harshan, N. K.; Salini, K. P.; Sunil, P. V. (Indian Journal of Fisheries, 2014)
The Self Help Groups (SHGs) mobilised in marine fisheries sector play pivotal role in reducing the indebtedness among marine fisherfolk. An effort is made in the present paper to assess the extent of indebtedness among marine fisherfolk in various sectors and to assess the role of SHGs on coastal rural indebtedness. The study was carried out in northern, central and southern coastal belts of Kerala State. Situational analysis was done through Participatory Learning and Action (PLA) in the selected locations in the above mentioned zones of Kerala and the sample respondents were selected from mechanised, motorised, traditional, secondary, tertiary and mariculture sectors. Data were collected through personal interview from members of 12 selected SHGs and nonmembers in these sectors comprising a total of 600 respondents. The level of indebtedness of members of SHGs was less compared to the nonmembers. Even if indebtedness was more in certain cases, the repayment capacity was found to be significantly improved in SHGs. There is an extreme necessity of strengthening the SHG ventures in the traditional, secondary and tertiary sectors in the state. It was also found that the SHGs ranked better in most of the major attributes in the perception of stakeholders. A comparative assessment of the sources of credit, the purposes of credit and the utilisation pattern of loans in the state also was undertaken to draw valid conclusions. Successful microfinance ventures documented can be used as a practical manual for mobilising SHGs in any key areas on a sustainable basis.